Hubungan Kepemimpinan Melayani (Servant Leadership) Dosen Terhadap Produktivitas Kerja Mahasiswa Keperawatan di Universitas Malahayati Kota Bandar Lampung - Devy Annieza Zahra; Usastiawaty C.A.S Isnainy; M. Arifki Zainaro (MAHESA : Malahayati Health Student Journal, 2024)
ABSTRACT Education plays a key role in shaping competent human resources characterized by the ability to compete in the global era. To create quality human resources and have work productivity requires an education, as it is crucial for refining individual development in mastering knowledge and work productivity. There are several factors influencing work productivity, including external factors such as leadership styles. Servant leadership, which nurtures and prioritizes the interests of followers over personal interests, is particularly suitable when exercised by professors towards students. Purpose to know the relationship between serving leadership and work productivity of nursing students at Malahayati University in the city of Bandar Lampung. The type of research used is quantitative, where the design employed in this study is an analytical survey with a cross-sectional approach. The population in this research consists of all nursing students at Malahayati University in the city of Bandar Lampung, who are in their 6th and 8th semesters, totalling 101 students as of January 2024. Therefore, the sample comprises 89 respondents. The sampling technique used in this study is Total Sampling. The analysis results indicate that the majority of lecturer’s exhibit non-serving leadership, and most nursing students are not productive. The p-value is 0.000 (<0.05), which means there is a significant relationship between the serving leadership of lecturers and the work productivity of students. The analysis results show a p-value of 0.000 (<0.05). There is a relationship between servant leadership of lecturers and the work productivity of nursing students at Malahayati University in the city of Bandar Lampung. It is advisable for lecturers to adopt more emotional and psychological approaches toward students. Additionally, students are encouraged not only to rely on external factors such as encouragement from lecturers but also to enhance their individual academic qualities. Keywords: Servant Leadership, Work Productivity, Nursing Students  ABSTRAK Pendidikan memegang peran kunci dalam membentuk sumber daya manusia yang baik yang ditandai oleh kompetensi untuk mampu bersaing di era global, Untuk menciptakan sumber daya manusia yang berkualitas dan memiliki produktivitas kerja membutuhkan suatu pendidikan, karena pendidikan sangat penting untuk menyempurnakan perkembangan individu dalam menguasai pengetahuan, produktivitas kerja, ada beberapa faktor yang berpengaruh terhadap produktivitas kerja yaitu faktor eksternal yang mencakup gaya kepemimpinan, gaya kepemimpinan melayani merupakan kepemimpinan yang mengayomi dan lebih mementingkan kepentingan pengikutnya dibandingkan kepentingan pribadi,kepemimpinan ini sangat cocok apabila dilakukan oleh dosen terhadap mahasiswa. Diketahui hubungan gaya kepemimpinan melayani terhadap produktivitas kerja mahasiswa keperawatan di universitas malahayati Kota Bandar Lampung. Jenis penelitian yang digunakan adalah kuantitatif dimana rancangan dalam penelitian ini menggunakan survey analitik dengan pendekatan cross-sectional. Populasi dalam penelitian ini adalah seluruh mahasiswa keperawatas universitas malahayati Kota Bandar Lampung semester 6 dan 8 berjumlah 101 pada bulan januari 2024, sehingga didapati sampel berjumlah 89 responden. Teknik sampling dalam penelitian ini adalah total sampling. Pada penelitian ini hasil analisis menunjukan sebagian besar kepemimpinan dosen tidak melayani, dan Sebagian besar mahasiswa keperawatan tidak produktif, p-value 0,000 (<0,05) yang berarti ada hubungan antara kepemimpinan melayani dosen terhadap produktivitas kerja mahasiswa, hasil analisis menunjukan nilai p-value 0,000 (<0,05). Ada hubungan antara kepemimpinan melayani dosen terhadap produktivitas kerja mahasiswa keperawatan di universitas malahayati Kota Bandar Lampung. Sebaiknya untuk dosen lebih melakukan pendekatan kepada mahasiswa secara emosional dan psikologis, dan untuk mahasiswa agar tidak hanya terpaku pada faktor eksternal seperti dorongan dari dosen, tetapi lebih mengembangkan mutu individunya di bidang akademis. Kata Kunci: Kepemimpinan Melayani, Produktivtas Kerja, Mahasiswa Keperawatan